EPISTEMOLOGI PENDIDIKAN ISLAM AL SYAIBANY DALAM PEMBELAJARAN AKHLAK - Asy-Syahida, Salma Nadhifa; Koestanti, Melinda; Irawan, Irawan (Raudhah - Proud To Be Professional, 2024)
This research aims to analyze Al-Syaibany's thinking related to moral education in the learning process. This study uses a qualitative approach with a library research design. The results of the study show that the basic principles of morality according to Al-Shaibany consist of six main points. First, the belief in the importance of morals in life. Second, morality is seen as a deep attitude in the human soul. Third, morality aims to achieve happiness in this world and the hereafter, both individually and in society. Fourth, the purpose of morality is to create happiness in this world and the hereafter for individuals and society. Fifth, morals must be in line with human nature. Sixth, moral theory is only considered perfect if it is supported by basic concepts such as conscience morality, moral compulsion, moral law, moral responsibility, and moral reward. In its relevance, moral education is a very important main instrument to be considered in policy making at all levels of education and institutions.